Battling for Human Rights and Social Justice: A Latina/o Critical Race Media Analysis of Latina/o Student Youth Activism in the Wake of 2006 Anti-immigrant Sentiment - Vélez, Veronica (Social justice, 2008)
Part of a special issue on Latino citizenship and social justice. A study was conducted to examine Latino youth activism in response to proposed immigration legislation in 2006. Data were obtained from an analysis of 108 articles about Latino youth activists from major U.S. newspapers between March 1 and May 31, 2006. Findings revealed that, although the papers portrayed some youth activism as positive, reporters mostly discredited it and reinforced pre-existing, mostly negative, ideas about young Latinos; references to “truancy” and “deviance” stopped just short of calling these young people criminals for leaving their schools, and went beyond suggesting they were naive or uninformed because of their youth. Findings suggested that these negative portrayals were due to the fact that these young people or their families come from another culture. Findings are discussed in detail.